Acetylcoumarin in cyclic and heterocyclic-containing coumarins: Synthesis and biological applications. (17th December 2022) - Hosseini Nasab, Narges; Azimian, Fereshteh; Kruger, Hendrik G.; Kim, Song Ja
Abstract: In design and development of bioactive compounds, coumarins as ubiquitous natural heterocyclic compounds have been widely used. In particular, the combination of the coumarin ring with various heterocycles provides opportunities towards generating novel multi-cyclic compounds with improved biological activity. In order to prepare cyclic and heterocyclic contained coumarins, a variety of synthetic pathways and conditions have been applied to create novel hybrid molecules which possess highlighted biological activities. The current review provides a comprehensive portrayal of using various methods, techniques, and reaction conditions for the synthesis of cyclic and 3, 4-heterocycle contained coumarins. The synthesis of different classes of compounds including coumarin-fused 3-membered cyclic, unsaturated five and six-membered heterocycles through different mechanisms and the outcomes achieved from such reactions are presented. This review sets out the observed biological activity of synthesized compounds and the future perspective in this area. The prepared compounds showed a range of activities such as antifungal, antimicrobial, anti-proliferative, and anti-inflammatory. It is hoped that this review brings some knowledge to interested researchers engaged in this area. Graphical abstract: Image 1